UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5 – 6 TAHUN MELALUI MEDIA KARTU KATA (PENELITIAN TINDAKAN KELAS DI TK PURI HASANA, BEKASI BARAT, 2021) - My, Wardah; Pujianti, Yuli (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
The main problem in this study is how to improve early reading skills through the use of word cards for group B students at Puri Hasana Kindergarten Perumnas 1 Kranji, West Bekasi. This study aims to determine the increase in the initial reading ability of students in group B at Puri Hasana Kindergarten Perumnas 1 Kranji West Bekasi after using word card media. This type of research is Classroom Action Research which consists of two cycles, each cycle is carried out in two meetings. The research procedure includes planning, implementation, observation and reflection. The subjects in this study were Group B TK Puri Hasana Perumnas 1 Kranji West Bekasi as many as 10 people. The results of this study can be concluded that the reading ability of children in group B TK Puri Hasna Perumnas 1 Kranji West Bekasi can be improved through word card activities. The increase in children's reading ability can be seen from the average reading observation results of pre-action children, which is 41.4%, in the first cycle it reaches 59.1% in the second cycle it reaches 84.3%. So the percentage of 84.3% has reached the achievement target with the Very Good Developing criteria (BSB). Based on the results of the research above, it was concluded that there was an increase in the initial reading ability of group B students at Puri Hasana Kindergarten Perumnas 1 Kranji West Bekasi after using word cards as media.